Bis(μ-cobaltoceniumselenolate-1:2κ2Se:Se)bis[bis(cobaltoceniumselenolate-κSe)mercury(II)] tetrakis(hexafluoridophosphate) acetonitrile disolvate - Daniel Menia (International Union of Crystallography, 2021)
The title compound, [Co6Hg2(C5H5)6(C5H4Se)6](PF6)4·2CH3CN or [Hg2(CcSe)6][PF6]4·2CH3CN (Cc = C10H9Co), was obtained as bright-orange needle-shaped crystals. It is a salt containing a tetracationic dimercury species with six cobaltoceniumselenolate ligands, four hexafluoridophosphate counter-ions and two acetonitrile solvent molecules. The cation (point group \overline{1}) has a bitetrahedral Hg2Se6 core with two bridging Se atoms and four terminal Se atoms.